Rancang Bangun Sistem Pakar Dalam Penentuan Jenis Penyakit Pada Hewan Sapi - Detyaputra Kusuma Mulya; Januar Wibowo; Waldy Permana Agastya (Jurnal Sistem Informasi Universitas Dinamika, 2012)
Livestock is one of the aspects that play a role in increasing state revenues. One of the animals are very much in breeding cows are animals. Because the cow has the benefit that pretty much started from the skin, meat and milk. In maintaining the cattle, the disease is one of the risks that must be faced. Just as a cow is suffering from certain diseases that can damage the quality of cow milk production. There is also a disease that can lead to miscarriage and even death in cattle, especially infectious disease. Cow disease was not a little, there is caused by bacteria, parasites and fungi. Of course this can not be allowed because it can be very detrimental to cattle owners. For it is necessary to act quickly and appropriately to the sick cow. Solutions to overcome the above problems is to use an expert system application in determining the type of the disease in cattle. By using the expert system application we can know the type of the disease quickly through existing symptoms in cattle and provide appropriate measures to mitigate them. Thus another disease affecting cattle can be controlled and not to spread and cause death in cattle. Keyword: System Administration, patient service, drug stocks